Medicina noviter inventa: physician knowledge and ars lulliana - Pereira, Michela (Itinerari, 2023)
This paper surveys the four texts on medicine written by Ramon Llull between 1274 ca. and 1303, stressing the author’s purpose to renew and rationalize scholastic medicine by applying his ars combinatoria to the full range of topics developed in the Galenic and Avicennian tradition. The Lullian attempt focused especially on the then debated problem of the graduation of drugs, which he tried to solve by means of a fully developed combinatory of the four elements and sixteen elementary mixtions. He also proposed the metaphorical use of medical exempla, as well as an integrated – albeit only sketchy – view of medicine and cosmology.